Novel 4DCT Method to Measure Regional Left Ventricular Endocardial Shortening Before and After Transcatheter Mitral Valve Implantation. Issue 4 (4th July 2021) - Colvert, Gabrielle M.; Manohar, Ashish; Contijoch, Francisco J.; Yang, James; Glynn, Jeremy; Blanke, Philipp; Leipsic, Jonathon A.; McVeigh, Elliot R.
ABSTRACT: Background: Regional left ventricular (LV) mechanics in mitral regurgitation (MR) patients, and local changes in function after transcatheter mitral valve implantation (TMVI) have yet to be evaluated. Herein, we introduce a method for creating high resolution maps of endocardial function from 4DCT images, leading to detailed characterization of changes in local LV function. These changes are particularly interesting when evaluating the effect of the TendyneTM TMVI device in the region of the epicardial pad. Methods: Regional endocardial shortening from CT (RSCT ) was evaluated in Tendyne (Abbott Medical) TMVI patients with 4DCT exams pre- and post-implantation. Regional function was evaluated in 90 LV segments (5 longitudinal x 18 circumferential). LV volumes and ejection fraction (EF) were also computed. A reproducibility study was performed in a subset of patients to determine the precision of RSCT measurements in this population. Results: Baseline and local changes in RSCT post TMVI were highly variable and extremely spatially heterogeneous. Both inter- and intra-observer variability were low and demonstrated the high precision of RSCT for evaluating regional LV function. Conclusion: RS CT is a reproducible metric which can be evaluated in patients with highly abnormal regional LV function and geometry. After TMVI, significant spatially heterogeneous changes in RSCT were observed in all subjects; therefore, it is unlikely that the functional state of TMVI patients can be fully described by changes in LV volume or EF. Measurement of RSCT provides precise characterization of the spatially heterogeneous effects of MR and TMVI on LV function and remodeling. Abbreviations: LV: Left Ventricle; MR: Mitral Regurgitation; TMVI: Transcatheter Mitral Valve Implantation; EP: Epicardial Pad; RSCT : CT Regional Endocardial Shortening; ED: End Diastole; ES: End Systole; EF: Ejection Fraction; LVOT: Left Ventricular Outflow Tract